From Aristotle to Heidegger a tour of the place to the spatiality of Dasein - Quenaya Mendoza, Carlos (2012)
This article is an essay of reading Aristotle’s notions of place, and spatiality of Dasein in Heidegger, focusing in Book IV of Physics and in paragraphs 22, 23 and 24 of chapter three of the first part of Being and Time. In addition, a reference to their particular metaphysical conceptions is made, and some significant relationships are tried to be highlighted without losing sight of the philosophical horizon that distinguishes both thinkers.